Adaptive differential current relay based on form/ripple factors for busbar current signals - R. A. Mahmoud (Scientific Reports)
Abstract This paper presents an adaptive protection algorithm that adjusts the tripping characteristics of the differential relaying schemes in response to changes in CT saturation levels and DC component content of fault currents. Moreover, the main protection function differentiates between internal and external faults with or without CT saturation. This is accomplished by estimating the appropriate tripping characteristic slope using form and ripple factors calculated for the current signals measured at the entering and exiting terminals of the protected equipment. The modified approach aims to achieve automatic resetting to inhibit the relay operation during external faults and to avoid any delay or restriction of the relay operation during severe internal faults due to the presence of harmonics. Numerous cases, including various types of internal and external faults with or without CTs saturation and DC component, are carried out on a typical power system simulated using the ATP platform. The proposed algorithm can be performed utilizing the MATLAB software, which can receive current measurements from the ATP simulator. The simulation results manifest the functional efficiency of the suggested technique under diverse operating and fault conditions and its ability to discriminate fault location. Additionally, the response time of the suggested technique is roughly 10.0 ms in the event of internal faults, which is also appropriate for preventing the technique from functioning in the case of non-fault or external fault disturbances. Furthermore, it is able to recognize CT saturation conditions, assess the degree of current distortion, and select which feeder CT is saturated. Besides, the outcomes demonstrate the extreme simplicity, effectiveness, stability, accuracy, and reliability of the proposed algorithm. Quantitative findings from the extensive case studies indicate that the estimated ratios of the protection’s accuracy, dependability, security, and reliability are greater than 99.40%. It is applicable to Smart Grids (SGs) and Substation Automation Systems (SAS), as the algorithm is one of the applications in digital protection relays/systems.